If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + -4 + 2a = -12 + 3a Reorder the terms: -4 + 2a + 2a = -12 + 3a Combine like terms: 2a + 2a = 4a -4 + 4a = -12 + 3a Solving -4 + 4a = -12 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. -4 + 4a + -3a = -12 + 3a + -3a Combine like terms: 4a + -3a = 1a -4 + 1a = -12 + 3a + -3a Combine like terms: 3a + -3a = 0 -4 + 1a = -12 + 0 -4 + 1a = -12 Add '4' to each side of the equation. -4 + 4 + 1a = -12 + 4 Combine like terms: -4 + 4 = 0 0 + 1a = -12 + 4 1a = -12 + 4 Combine like terms: -12 + 4 = -8 1a = -8 Divide each side by '1'. a = -8 Simplifying a = -8
| n+8+2n-4=7+4n-20 | | x+2(-2)=-1 | | 8(4+7n)-6n=332 | | 6=k+7 | | 5x+5-6x=-x+5 | | y-5/y=10/8 | | m-15/4-4m-4/5=2 | | 25t^2+30x+7=0 | | y-5/5=10/8 | | 4+7+5x=0 | | 6(x+7)=5(x-7)+x | | 3x+2x+10=5x+5 | | 11x^2+30x-9=0 | | 6(x-9)x=7(x-8)+2 | | 5(3a-b)-7(3b-7a)= | | 9x+7y=-70 | | 3x+2x+10=5x+1 | | 8m(m+3)=2m-5 | | -4/5t+2/5=2/3 | | 4x-2(x-5)=2(x+1)+9 | | 9x+3-3x-5=30 | | 9y+9=45 | | 2y+3(y-4)=6y-3(y-10) | | -5(y-4)=40 | | 192z^2-20x-2=0 | | 7x-5+2x=3+4x+12 | | 4y+4(y-8)=8y-2(y-10) | | x(x-2y)-6= | | 9x^2+486=0 | | 15x^2-41x+22=0 | | 4(-1+-2y)-4y=20 | | -3(2m-2)-2(m+2)= |